Topographic Evolution of Von Kármán Crater Revealed by the Lunar Rover Yutu‐2. Issue 22 (22nd November 2019) - Di, Kaichang; Zhu, Meng‐Hua; Yue, Zongyu; Lin, Yangting; Wan, Wenhui; Liu, Zhaoqin; Gou, Sheng; Liu, Bin; Peng, Man; Wang, Yexin; Niu, Shengli; Zhang, Jinhai; et al.
Abstract: Chang'e‐4 (CE‐4) achieved the first farside landing in Von Kármán crater. In the landing site, linear features have been identified previously from SLDEM and considered to be ejecta from the neighboring Finsen crater. The 5 cm grid spacing digital elevation model of the landing site, generated from the rover's panoramic images, provides more details of the rugged terrain. We further interpret the superimposition of NE‐SW ejecta from Finsen crater on the underlying SE‐NW dome‐like surface relief from Alder crater. The landing site is ~70 m higher than the mare basalts within Von Kármán crater. Numerical simulations predict ~30 and ~35 m ejecta deposited at the landing site from Finsen and Alder craters, respectively. The good agreement between the digital elevation model data and ejecta predicted thickness reveals the topographic evolution of Von Kármán crater, indicating that the rover‐measured material is excavated from Finsen crater with possible contributions from Alder crater. Plain Language Summary: Chang'e‐4 probe, including a lander and a rover, achieved the first farside landing in Von Kármán crater within the South Pole‐Aitken basin (SPA). The SPA is the largest and oldest impact basin on the Moon and is thought to have exposed lunar mantle materials according to numerical simulations. The in situ explorations at the landing site by the Yutu‐2 rover can reveal information about lunar deep materials and shed light on the early impacting history of the Solar System. Here, we present a detailed topographic analysis of the landing site using a rover‐image‐derived finer grid spacing DEM, existing orbital‐data‐derived DEMs, and numerical simulations. The results reveal the topographic evolution of the SPA and demonstrate that the surface material explored by the Yutu‐2 rover is lunar deep interior material excavated from Finsen crater with possible contributions from Alder crater rather than the underlying mare basalt. Key Points: Linear ejecta features are identified and measured on a 5 cm grid spacing DEM generated from Yutu‐2's stereo images and existing DEMs Numerical impact simulations predict ~30 and ~35 m ejecta deposited at the landing site from Finsen and Alder craters, consistent with the topographic difference The surficial material measured by Yutu‐2 was ejecta from the floor of South Pole‐Aitken basin, not the beneath mare basalts at the landing site